Organic versus integrated apple growing: I. differences in soil and leaf parameters - Nagy, P. T.; Szabó, Z.; Nyéki, J.; Gonda, I.; Holb, I. J. (International Journal of Horticultural Science, 2009)
The aim our study was to establish whether significant differences in nutrients uptake and quality of soil and leaf exist between organic and integrated grown apples. The study was performed at the orchard Fruit Research Station, University of Debrecen, at Debrecen-Pallag during 2002–2004. Macro and micro elements were measured in soil and plant samples. Analyses of variance of soil nitrogen data indicated highly significant differences between the two management systems (P < 0.001) for each examined nitrogen fraction. Analyses of variance of soil phosphate data indicated significant differences (P < 0.05) between the two management systems for orto-PO4 3– contents. Our data indicated that highly significant differences between the two management systems (P < 0.001) for magnesium, copper, and zinc; while significant differences between the two management systems was at P = 0.007 for calcium. Three year’s data of leaf phosphorus, sulphur and zinc were not shown significant differences between production systems. Nevertheless manganese and copper contents of leaves were higher in the organic orchard compared to the integrated one.